Targeting mutant p53 in cancer: from mechanistic insights to therapeutic strategies - Wu, H. H.; Leng, Sarah; Eisenstat, David D.; Sergi, Consolato; Leng, Roger (Université d'Ottawa | University of Ottawa, 2026)
Abstract The tumor suppressor p53, often referred to as the “guardian of the genome,” is mutated in more than half of human cancers. These mutations have a significant impact on cancer biology and response to therapy. p53 mutations involve a range of changes that interfere with DNA binding, eliminate tumor suppressor functions, and, in many cases, confer dominant-negative or gain-of-function characteristics that actively promote oncogenesis. These mutations are closely linked to poor clinical outcomes and resistance to standard treatments. This review examines the impact of p53 mutations on cancer therapy in various ways. In chemotherapy and radiotherapy, loss of wild-type p53 impairs DNA damage responses, whereas mutant forms often contribute to treatment resistance. Additionally, p53 status influences responses to targeted therapies and immunotherapies, thereby affecting patient outcomes and prognoses. Importantly, ongoing clinical trials are beginning to integrate p53 mutational status as a predictive biomarker for therapy selection. Strategies aimed at restoring p53 activity are gaining increasing popularity in the development of treatments. These approaches include gene therapy to reintroduce the wild-type gene, targeted degradation of mutant p53 proteins, and small molecules designed to refold or reactivate mutant p53. In addition, synthetic lethality frameworks are being utilized to exploit vulnerabilities specific to tumors with p53 mutations, as well as interventions that target downstream effectors of p53 pathway. Together, these strategies represent a significant shift in precision oncology. Graphical Abstract